Al-Hurriyah fi Manzur Ma’had Darussalam Gontor - Khasib Amrullah; Fatimah Azzahra (University of Darussalam Gontor, Indonesia, 2019)
Pondok Modern Darussalam Gontor is one of the educational institutions inIndonesia that has given a lot of contribution in coloring the national life mosaic. With the concept and purpose of the education which is very supporting in the formation of the ummah, because it is based on Islamic law which refers to the Qur’an and Hadith. It also has a form of life philosophy that guarantees the progress of the nation, named by the five spirit and mottoes of Pondok Modern. One of the most important philosophies in Gontor is freedom and free thinking. Because the freedom and instilled by Gontor aims to make the students select wisely their future life based on Islamic law. However, there are some views that blame this kind of philosophy, it comes from those who have not understood deeply the purpose of Gontor’s education, both outsiders, students, and even graduation. They think that freedom in Gontor caused the student become Liberal, while the essence was no. So, this article wants to examine the essential concept of freedom in the perspective of Pondok Modern Darussalam Gontor.